Disrupting glioblastoma networks with tumor treating fields (TTFields) in in vitro models - Schlieper-Scherf, Steffen; Hebach, Nils R.; Hausmann, David; Domínguez Azorín, Daniel; Hoffmann, Dirk C.; Horschitz, Sandra; Maier, Elena; Koch, Philipp; Karreman, Matthia A.; Etminan, Nima; Ratliff, Miriam (Journal of neuro-oncology, 2024)
This study investigates the biological effect of Tumor Treating Fields (TTFields) on key drivers of glioblastoma’s malignancy—tumor microtube (TM) formation—and on the function and overall integrity of the tumor cell network.
Philipp Koch ist in der Verfasserangabe fälschlich als Philip Koch geschrieben
Online veröffentlicht: 1. August 2024
Gesehen am 05.11.2024